PREVALENCE OF TRAUMATIC DENTAL INJURIES AMONG 1–14-YEAR-OLD CHILDREN IN TERTIARY CARE CENTER OF NEPAL - Shah, Priyanka; Khanal, Sanskriti (Journal of Chitwan Medical College, 2024)
Background: Traumatic dental injuries have now become a leading health issue due to their high prevalence and major impact on children’s well-being. These dental injuries may result in esthetic, psychosocial, functional, therapeutic problems and lead to irreversible damage to dentition and supporting structure. This study was aimed to evaluate the prevalence of traumatic dental injuries in children from 1 to 14 years of age. Methods: This cross-sectional study was conducted among 1–14-year-old children who visited Department of Pedodontics, Nepal Medical College during the study period. The oral examination was done with the help of a dental mirror and explorer and were evaluated for age, gender, type of trauma (based on history/clinical examination) and involvement of hard and soft issue. The traumatic dental injury (hard tissue injury) was assessed using Ellis and Davey’s classification. Results: Out of the 2,391 patients examined during the six months duration, 31 (1.29%) patients presented with traumatic dental injuries, among which male, 18 (58.1%) presented with more traumatic dental injuries than females 13 (41.9%). The involvement of hard tissue injury (64.5%) was more than soft tissue injury (12.9%). Both the permanent and deciduous maxillary central and lateral incisors were most frequently involved than other teeth. (Permanent maxillary incisors 38.7 %; Deciduous maxillary incisors 41.9%). Conclusions: In this study the teeth that was more frequently involved was maxillary anterior teeth. The most common reason for trauma was fall injury.